[PP.30.24] FAMILIAL FIBROMUSCULAR DYSPLASIA COEXISTING WITH MOYA-MOYA SYNDROME FOUND IN PATIENTS ENROLLED INTO ARCADIA-POL STUDY. (September 2017) - Hanus, K.; Peczkowska, M.; Warchol-Celinska, E.; Florczak, E.; Swiatlowski, L.; Jozwik-Plebanek, K.; Januszewicz, M.; Talarowska, P.; Aniszczuk, A.; Kowalik, K.; Ziebka, J.; Kabat, M.; et al.
Abstract : Objective: Fibromuscular dysplasia (FMD) is non-inflammatory and non-atherosclerotic arteriopathy that may involve multiple vascular beds and may result in artery stenosis, occlusion, aneurysms or arterial dissection. It has been reported that very rarely FMD may coexist with other vascular abnormalities including Moya-Moya syndrome. The aim of this study is to present a case of familial FMD coexisting with Moya-Moya syndrome revealed in patients enrolled to ARCADIA-POL study. Figure. No caption available. Design and method: Out of 182 patients enrolled into ARCADIA-POL study since January 2015 we evaluated 144 patients with confirmed FMD. All patients underwent detailed clinical evaluation including whole body angio-CT. Results: The genealogical tree of the family is presented in Figure 1. We evaluated a 28-year-old woman with a history of renal multifocal FMD and hypertension. Whole body angio-CT revealed FMD in 4 vascular beds – both renal arteries with no significant stenosis, cervical arteries, intracranial arteries and celiac trunk. For the further evaluation of diffused abnormalities of intracranial and cervical arteries found in angio CT classic angiography was performed suggesting Moya-Moya syndrome. Because of high suspicion of familial FMD we also evaluated petients' first-degree relatives. On the basis of evaluation according to the ARCADIA-POL protocol renal FMD was found in both sisters and father, cervical FMD was found in two sisters, mesenteric and celiac trunk FMD - in one sister and father. The abnormalities of intracranial arteries were confirmed in both sister in classical angiography – in one sister the suspicion of Moya-Moya syndrome was raised. Additionally we evaluated further family members revealing a presence of intracranial aneurysm in fathers' sister. In other 5 family members the presence of FMD lesions were excluded in whole-body angio-CT. Conclusions: In summary we report a case of familial FMD in 4 family members – in each member FMD lesions were present in more than one vascular bed. Also our study showed that systematic evaluation of patients based on the whole-body angio-CT revealed a rare association between FMD and Moya-Moya syndrome. In contrast to previous reports we documented coexistence of FMD with Moya-Moya syndrome in two family members.